2014
DOI: 10.1371/journal.pone.0086203
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Gifsy-3 and of Variants of ST64B and Gifsy-1 Prophages amongst Salmonella enterica Serovar Typhimurium Isolates: Evidence that Combinations of Prophages Promote Clonality

Abstract: Salmonella isolates harbour a range of resident prophages which can influence their virulence and ability to compete and survive in their environment. Phage gene profiling of a range of phage types of Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) indicates a significant level of correlation of phage gene profile with phage type as well as correlation with genotypes determined by a combination of multi-locus variable-number tandem repeat (VNTR) typing and clustered regularly interspac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Schmieger and co-workers (Schicklmaier et al , 1998; Schmieger, 1999) found that 173 S. enterica serovar Typhimurium isolates released a minimum of 136 functional phages, and the commonly used laboratory Typhimurium isolate LT2 carries four intact, fully functional prophages (Yamamoto, 1967 & 1969; Yamada et al , 1986; Figueroa-Bossi and Bossi, 1999; McClelland et al , 2001). Many studies have also shown that prophage content accounts for a substantial part of the natural variation among Salmonella isolates ( e.g., Reen et al , 2005; Cooke et al , 2007; Drahovska et al , 2007; Rychlik et al , 2008; Fricke et al , 2011; Moreno Switt et al , 2012; Pang et al , 2013; Bobay et al , 2014; Hiley et al , 2014; Switt et al , 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Schmieger and co-workers (Schicklmaier et al , 1998; Schmieger, 1999) found that 173 S. enterica serovar Typhimurium isolates released a minimum of 136 functional phages, and the commonly used laboratory Typhimurium isolate LT2 carries four intact, fully functional prophages (Yamamoto, 1967 & 1969; Yamada et al , 1986; Figueroa-Bossi and Bossi, 1999; McClelland et al , 2001). Many studies have also shown that prophage content accounts for a substantial part of the natural variation among Salmonella isolates ( e.g., Reen et al , 2005; Cooke et al , 2007; Drahovska et al , 2007; Rychlik et al , 2008; Fricke et al , 2011; Moreno Switt et al , 2012; Pang et al , 2013; Bobay et al , 2014; Hiley et al , 2014; Switt et al , 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Integrated prophage can block phage DNA penetration into bacterial cell as it codes blocking proteins that are localized at the membrane/cell wall level of the host cell. A strong relation between the integrated prophages and the phage type was observed [ 17 ]. For example, S. Typhimurium strain LT2 contains 4 prophages; (Fels-1, Fels-2, Gifsy-1 and Gifsy-2) [ 18 ], S. Typhimurium strain UK-1 contains 3 prophages, two that are homologous to those in LT2 (Gifsy-1, Gifsy-2) in addition to ST64B prophage [ 19 ] and S. Typhimurium strain SL1344 contains 4 prophages; 3 homologs of those in LT2 (Gifsy-1, Gifsy-2, Fels-2) and ST64B [ 20 ] and each of these strains has a distinct typing pattern as LT2, UK-1 and SL1344 strains belong to DT4, DT1 and DT44 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Prophages Gifsy-1 and Gifsy-2 are found in all major S. Typhimurium lineages [55] and were carried by most of the Colombian S. Typhimurium isolates (Fig. 3).…”
Section: Accessory Genomementioning
confidence: 99%